Kingianins O-Q: Pentacyclic polyketides from Endiandra kingiana as inhibitor of Mcl-1/Bid interaction - Azmi, M.N.; Péresse, T.; Remeur, C.; Chan, G.; Roussi, F.; Litaudon, M.; Awang, Khalijah (Elsevier, 2016)
A phytochemical study of the EtOAc-soluble part of the methanolic extract of the bark of Endiandra kingiana led to the isolation of three new pentacyclic kingianins as racemic mixtures, kingianins O-Q (1-3), together with the known kingianins A, F, K, L, M and N (4-9), respectively. The structures of the new kingianins 1-3 were determined by 1D and 2D NMR analysis in combination with HRESIMS experiments. Kingianins A-Q were assayed for Mcl-1 binding affinity. Kingianins G and H were found to be potent inhibitors of Mcl-1/Bid interaction. A structure-activity relationship study showed that potency is very sensitive to the substitution pattern on the pentacyclic core. In addition, in contrast with the binding affinity for Bcl-xL, the levorotatory enantiomers of kingianins G, H and J exhibited similar binding affinities for Mcl-1 than their dextrorotatory counterparts, indicating that the two anti-apoptotic proteins have slightly different binding profiles.